COSMOGENICAL NOTIONS IN THE QUR’AN: THE METAPHYSICAL ORIGIN OF THE PHYSICAL COSMOS - Sabbir Hossain; Mazlan Ibrahim; Indriaty Ismail (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
Upon distinguishing cosmogony – the ultimate origin of the cosmos – from cosmogony – the early state of the cosmos, the paper presents a Qur’anic account of cosmogeny based on three relevant verses. The articulated Qur’anic cosmogeny of the paper affirms the doctrine of creatio ex nihilo and reveals the metaphysical origin of the cosmos. A number of cosmogenical principles are also presented in the article, which further demonstrate and reaffirm the theocentric nature of Qur’anic as well as Islamic cosmologies. The denouncement of absolute nothingness as per the newly-formulated cosmogeny and its principles presented in the paper certainly indicates the fundamental difference between the natures of the reality and the Ultimate Reality in Islam.